A GLOBAL RESEARCH TREND ON FRANCHISEE IN FRANCHISING LITERATURE REVIEW: A BIBLIOMETRIC ANALYSIS - Hien Thi Thao Bui; Manimekalai Jambulingam, (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
Franchising has become a worldwide international business activity. Companies have moved from conventional business models to multinational ones since the beginning of the twenty-first century to leverage their profitable performance and improve their competitive edge. Franchising is the best method for businesses to broaden into new areas. Franchisees play an important role in supporting franchise companies in expanding into new markets by providing valuable resources. This paper aims to provide an overview of academic research on franchisees in the franchise literature. An extensive bibliometric analysis, including bibliometric performance analysis and a graphic mapping of the references in this area, was carried out to achieve this. This research investigates journals, documents, authors, organizations/ institutions, and countries. The study employs various bibliometric metrics, such as the number of publications and citations to conduct the franchisee research. In addition, the VOS viewer is used to map the bibliographic content graphically. The graphical analysis uses co-citation, bibliographic coupling, and keyword co-occurrence. The findings of both studies are consistent, indicating that the United States is the most influential country in franchisee research, as it is home to the most influential authors and institutions in the field. Furthermore, the field's global growth has been observed and is expected to continue. Our study is insightful and complimentary since it covers most of the important aspects of franchisee research.